1992
DOI: 10.1128/jcm.30.5.1315-1316.1992
|View full text |Cite
|
Sign up to set email alerts
|

Serological cross-reactions between Escherichia coli O157 and other species of the genus Escherichia

Abstract: The antigenic relatedness ofEscherichia coli 0157 and four sorbitol-negative species of the genus Escherichia was examined. Isolates of Escherichia hermannii, E. fergusonii, E. vulneris, and E. blattae were tested in the tube agglutination assay by using polyclonal antisera and in the slide agglutination assay by using latex reagents. Only four isolates (17%) of E. hermannii exhibited serological cross-reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…However, non-STEC strains of this serogroup will also be detected and non-STEC serogroup 0157 strains are rather common in meats (Heuvelink et al 1996). Moreover, antigenically-related organisms, such as Citrobacter freundii, may carry the 0157 antigen (Bettelheim et al 1993), and E. hermannii may be agglutinated by 0157 antisera (Rice et al 1992). Somatic antibody cross-reactions have also been noted with bacteria of different genera, including DETECTION AND ISOLATION OF STEC 137S Salmonella group N, some Yersinia enterocolitica and Brucella spp., resulting in false-positive reactions (Okrend et al 1990c;Johnson et al 1995a).…”
Section: Immunological Detection Systemsmentioning
confidence: 99%
“…However, non-STEC strains of this serogroup will also be detected and non-STEC serogroup 0157 strains are rather common in meats (Heuvelink et al 1996). Moreover, antigenically-related organisms, such as Citrobacter freundii, may carry the 0157 antigen (Bettelheim et al 1993), and E. hermannii may be agglutinated by 0157 antisera (Rice et al 1992). Somatic antibody cross-reactions have also been noted with bacteria of different genera, including DETECTION AND ISOLATION OF STEC 137S Salmonella group N, some Yersinia enterocolitica and Brucella spp., resulting in false-positive reactions (Okrend et al 1990c;Johnson et al 1995a).…”
Section: Immunological Detection Systemsmentioning
confidence: 99%
“…Interestingly, the physical structure of the two LPS types has been shown to be quite distinct (Chart et al 1991b) Strains of E. coli O157:H7 ferment sorbitol only slowly and utilize this sugar very little during a 24 h incubation period (Wells et al 1983;March and Ratnam 1986). However, certain strains of E. hermannii are also poor sorbitol-fermenting and with a latex agglutination test (Rice et al 1992), were shown to cross-react with E. coli O157, probably because some strains of E. hermannii have the sugar sequence 4amino-4,6-dideoxy-a-D-mannopyranoside in their LPSs. The possibility arises that infections caused by strains of E. hermannii might be misdiagnosed based on E. coli O157 serology alone.…”
Section: E Coli O157 Lipopolysaccharide: Antibody Cross-reactionsmentioning
confidence: 99%
“…The possibility arises that infections caused by strains of E. hermannii might be misdiagnosed based on E. coli O157 serology alone. However, as only a proportion of strains of E. hermannii share LPS epitopes with E. coli O157 (Rice et al 1992) and infections caused by E. hermannii are rare, it seems unlikely that infections caused by E. hermannii would be confused with cases of HUS caused by E. coli O157:H7.…”
Section: E Coli O157 Lipopolysaccharide: Antibody Cross-reactionsmentioning
confidence: 99%
“…We report a between E. coli 0157:H7 and other microbial species, includsimilar sensitivity for cells inoculated into beef. Sensitivity ing E. hermannii, Salmonella 030 strains, Y enterocolitica 09, depends to some extent on the quality of the fluorescent and Brucella species, has been reported (2,20,27,32). The antibody.…”
Section: A Rmentioning
confidence: 99%